Game-Theoretic Models of Green Products in a Two-Echelon Dual-Channel Supply Chain under Government Subsidies. (28th May 2020) - Lou, Zhenkai; Lou, Xuming; Dai, Xiaozhen
Abstract : This paper deals with issues concerning green subsidies of government and optimal decisions of a manufacture and dual-channel retailers in a two-echelon dual-channel supply chain. Both a decentralized supply chain and a centralized supply chain are considered. Sufficient and necessary conditions for guaranteeing that the two supply chains run normally under government subsidies are proposed. For the decentralized supply chain, a three-layer model is constructed according to different priorities of the four participants. Both Bertrand game and Stackelberg game are involved. For the centralized supply chain, a two-layer model is given. Decision models of the government under a financial budget are developed for maximizing the green degree of each case. It is shown that the green degree of the product of the centralized supply chain is always higher than that of the decentralized supply chain. Meanwhile, the total profit of the centralized supply is also higher. Finally, a numerical illustration is presented to visualize the discussed models and make some supplements.